A unique core stability training program improves throwing velocity in female high school athletes - Seiler, S.; Sæterbakken, A. (Medicine & Science in Sports & Exercise, 2008)
PURPOSE: To determine the impact of a Sling Exercise Training (SET) core stability program on maximal throwing velocity in high school age female team handball players. METHODS: 28 female team handball players (16.6±0.3 yrs, 63±6 kg, 169±7 cm) were initially divided into an SET training group (n= 15) and a control group that performed their normal training (n=13). After loss to post testing, 14 SET trained (SET) and 9 control athletes (CON) were compared. Before and after the training period, throwing velocity (600 g handball, average of three best throws) was determined from a penalty shot position using a photo cell array, along with one legged balance, unstable push-up strength, and two weak link tests. The SET group performed 6 closed kinetic chain, unstable exercises 2.wk-1 for 7 weeks. RESULTS: Averaged throwing velocity increased 4.9% from 17.9±1.8 to 18.8±1.5 m·s-1 in SET (p<0.01), but was unchanged in CON 17.2±1.4 to 17.0±1.3 m·s-1 (p>0.05). Functional strength measured as modified pushups to failure with arms in slings increased in SET from 21±5 to 37±10 (p<0.001) vs from 11±7 to 16±9 in CON. One legged balance was not significantly improved after the intervention in either group. CONCLUSIONS: Core stability for an athlete may be defined as the ability of the hips and trunk to resist rotational torque. A strong and stable core region may be an important precondition for generating high rotational velocity in multi-segmental movements. The results of this study suggest that core stability training using closed kinetic chain exercises performed in unstable slings can significantly improve maximal throwing velocity.